Program Coordination and Synergy of the Foreign Supervision Team (Tim Pora) in Cianjur Regency - Rachmat, Rachmat (CV. Inara, 2021)
This study aims to find (identify) and determine problems related to the arrival of foreigners in Cianjur Regency. Furthermore, this research wants to set goals to be achieved. Of course, with the formation of the Pora Team, we want cooperation and coordination as well as synergy between related agencies. Third, the purpose of this study was to determine the communication strategy of the Pora Team in order to deal with the presence and activities of foreigners in the Cianjur Regency area. This study uses a qualitative approach with a post-positivistic paradigm. The method used is a case study. The models used are Assifi and French models. The result of this research is that the Pora Team analyzed various cases related to foreigners who came to Indonesia, especially Cianjur. The Sukabumi Class II Immigration Office released data on the number of Foreign Citizens (WNA) holding Permanent Stay Permit Cards (KITAP) who reside and have activities in Sukabumi and Cianjur. Apart from mixed marriages, not a few foreigners have the status of workers. There are 65 foreigners holding KITAP Cianjur Regency. The purpose of establishing the Pora Team is to supervise foreigners who come to Cianjur Regency, as an effort to prevent violations of regulations by foreigners in Cianjur Regency. The Pora Team's strategy-setting activities cover a variety of activities. These activities are in the form of (1) audience analysis, (2) selecting media, (3) developing messages, (4) implementing programs, (5) conducting monitoring and evaluation. The audience analysis in this case is foreigners. These foreigners have various kinds of arrival purposes such as tourism, socio-cultural visits, government, social and even for work. The Pora team in carrying out their duties collaborates with the Media. The Pora team coordinates with various government organizations. In carrying out its programs, apart from carrying out the duties and functions of the Pora Team, it can also carry out joint operations if needed. In conducting monitoring and evaluation, the results of joint operations are reported directly in writing. The report is submitted to the Chairman of the Pora Team no later than 7 (seven) days from the time the joint operation was carried out. The Pora team also has a map of the supervision of foreigners, solving problems of the existence and activities of foreigners, implementing and regulating relations and cooperation in the framework of controlling foreigners, preparing joint operation plans that are special or incidental in nature.